ENGLISH TEACHING STRATEGIES USED AT JILC IN ATTRACTING CUSTOMERS’ INTEREST - Reswara, Adinata Rangga; Jefri, Riny; Abdullah, Abdullah (Universitas Negeri Makassar, 2025)
This research uses descriptive qualitative method that aims to identify and describe English teaching strategies at JILC, which stands for Jakarta Intensive Learning Centre that can attract customers’ interest. The subjects of this research are English tutors and customers, namely students of JILC Perintis branch. Data were obtained through interviews with two English tutors and an online survey to JILC pupils regarding their interest in learning using the teaching strategies applied by the English tutors. From the results of the research, the customers are more interested in the Learning from Informational Text strategy in reading comprehension and memorizing vocabulary lessons.